1978
DOI: 10.1093/jnci/60.4.925
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of a Poorly Differentiated Human Adenocarcinoma to Ascites Form With Invasion and Metastasis in Nude Mice: Brief Communication

Abstract: Cells (1 X 10(7)/0.5 ml) from a Borrmann type III poorly differentiated adenocarcinoma of the human stomach were injected ip into nude mice. The injection resulted in ascites carcinoma with invasion (carcinomatous peritonitis) and liver metastasis. The inoculum was obtained from subcutaneous tumors at passage 9 in nude mice that had received serial transplants from the patient with Borrmann type III poorly differentiated adenocarcinoma of the stomach. Serial transfers of 1.5 X 10(6) dispersed cancer cells/0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…(1976), who observed metastasis of a malignant hamster tumor transplant only when the tumors had grown to a large size and had penetrated th-body wall. Similarly, Takahashi et al (1978) and Kyriazis et a/. (1978), observed that metastasis can be induced by the simple expedient of using the intraperitoneal, rather than subcutaneous, route of tumor transplant.…”
Section: Discussionmentioning
confidence: 89%
“…(1976), who observed metastasis of a malignant hamster tumor transplant only when the tumors had grown to a large size and had penetrated th-body wall. Similarly, Takahashi et al (1978) and Kyriazis et a/. (1978), observed that metastasis can be induced by the simple expedient of using the intraperitoneal, rather than subcutaneous, route of tumor transplant.…”
Section: Discussionmentioning
confidence: 89%
“…Some tumor cells implanted subcutaneously into the cranial aspect of the nude mouse grow faster and produce more metastases than tumor cells implanted subcutaneously into the posterior body aspect [50]. The intraperitoneal injection of human solid tumor cells can produce ascitic growth with local infiltration followed by production of distant metastases [43,51,52]; these very same tumor cells, however, were not invasive when implanted subcutaneously. Similarly, lack of invasion in an HCC tumor line was associated with a host response manifested by formation of a dense capsule composed of connective tissue.…”
Section: The Influence Of the Organ Environment On The Invasive Phenomentioning
confidence: 99%
“…Multifocal metastases and widespread carcinomatosis resulting from the i.p. route of tumor cell injection have been attributed to improved tumor vascularity and the absence of the restrictive fibrous sheath (71,73). Recently, Witte and Ber (77) reported the improved growth of hybridoma cells injected into the spleens of recipient mice, and consideration of these findings led Kozlowski et al (65) to inject human tumor cells into nude mice by different routes, including the spleen.…”
Section: The Metastatic Behavior Of Human Tumor Cell Lines In Nude Micementioning
confidence: 99%